2020
DOI: 10.1016/j.jcrc.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of critical care services in hospitals accredited for training in a lower-middle income country: Pakistan

Abstract: Purpose To describe the extent and variation of critical care services in Pakistan. Materials and methods A cross-sectional survey was conducted in all intensive care units (ICUs) recognised for postgraduate training to determine administration, infrastructure, equipment, staffing, and training. Results There were 151 hospitals recognised for training, providing 2166 ICU beds and 1473 ventilators. Regional distribution of ICU beds per 100,000… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 16 publications
(20 reference statements)
0
32
0
Order By: Relevance
“…9 Despite many structural changes in the residency program including less duty hours and organized grid system in many hospitals for the allotment of operative procedures to all the residents, residents always complain of having less cutwork as compared to his/her fellow resident. 10 In order to assess the perceptions of general surgical residents towards general surgery residency in Pakistan, this study was carried out to identity the factors and problems faced by general surgical residents during their 4 years of general surgical residency training in the Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…9 Despite many structural changes in the residency program including less duty hours and organized grid system in many hospitals for the allotment of operative procedures to all the residents, residents always complain of having less cutwork as compared to his/her fellow resident. 10 In order to assess the perceptions of general surgical residents towards general surgery residency in Pakistan, this study was carried out to identity the factors and problems faced by general surgical residents during their 4 years of general surgical residency training in the Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…PRICE provides real-time reporting on the epidemiology, severity of illness, treatment, microbiology, and outcomes of intensive care unit (ICU) patients alongside information regarding the workforce, unit activity, unit acuity, and resource utilization in the ICU. Work already undertaken by PRICE has identified wide regional disparity in the availability of critical care resources [ 11 ]. Similarly, characterization of the current pandemic in relation to available resources is an essential tool in the management of an outbreak [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…With no global benchmark for the number of hospital beds in relation to population, 7 the functional critical bed capacity in Pakistan is 0.71 per 100,000 population, lesser than the neighboring countries. 8 Findings from the nationwide survey, held during 2017-2018 in 157 intensive care units (ICUs) across the country, revealed that 54% of the ICUs had a one-to-one nurse-to-bed ratio for ventilated patients. 8 Concerning the availability of one-to-one nurse-to-bed ratio, this ranged from 56.5% having a 1:1 availability in Punjab, compared to 0% in Azad Jammu and Kashmir.…”
mentioning
confidence: 99%
“…8 Findings from the nationwide survey, held during 2017-2018 in 157 intensive care units (ICUs) across the country, revealed that 54% of the ICUs had a one-to-one nurse-to-bed ratio for ventilated patients. 8 Concerning the availability of one-to-one nurse-to-bed ratio, this ranged from 56.5% having a 1:1 availability in Punjab, compared to 0% in Azad Jammu and Kashmir. Ventilator-to-bed ratio of 1:1 was observed in 52% of the ICUs, with variations reported across the provinces.…”
mentioning
confidence: 99%
See 1 more Smart Citation